Multi-dimensional cubic symmetric block cipher algorithm for encrypting big data - Omar A. Dawood; Othman I. Hammadi; Khalid Shaker; Mohammed Khalaf (Institute of Advanced Engineering and Science, 2020)
The advanced technology in the internet and social media, communication companies, health care records and cloud computing applications made the data around us increase dramatically every minute and continuously. These renewals big data involve sensitive information such as password, PIN number, credential numbers, secret identifications and etc. which require maintaining with some high secret procedures. The present paper involves proposing a secret multi-dimensional symmetric cipher with six dimensions as a cubic algorithm. The proposed algorithm works with the substitution permutation network (SPN) structure and supports a high processing data rate in six directions. The introduced algorithm includes six symmetry rounds transformations for encryption the plaintext, where each dimension represents an independent algorithm for big data manipulation. The proposed cipher deals with parallel encryption structures of the 128-bit data block for each dimension in order to handle large volumes of data. The submitted cipher compensates for six algorithms working simultaneously each with 128-bit according to various irreducible polynomials of order eight. The round transformation includes four main encryption stages where each stage with a cubic form of six dimensions.